Description of three new species of Ooencyrtus (Hymenoptera: Encyrtidae) from China - Zhang, Xu; Zhang, Yan-Zhou; Wang, Ying; Chen, Fu-Qiang; Yu, Fang; Zhou, Qing-Song (Zootaxa, 2014)
Hymenoptera parasitoids of Megaloptera, particularly the family Corydalidae, are rarely found. Ooencyrtus Ashmead is a genus that attacks eggs of many orders of Insecta, including Megaloptera. Here, three species, O. longicauda sp. n., O. noyesi sp. n. and O. protohermeasis sp. n. are described. Two of them, O. longicauda and O. protohermesis were reared from eggs of corydalids (Megaloptera: Corydalidae). The three new species and O. yoshidai Noyes & Hirose are included in the newly established protohermesis species-group of Ooencyrtus because of shared similar morphological characters and what is apparently a shared host family (unknown for O. noyesi).